Green Awareness and Green Attitude as Predictors of Green Purchase Intention: A Study on Green Cosmetic Consumers in Indonesia - Putra, Wira Pramana; S, Putri Paulina; Shevana, Nabella Zahra (Journal of Economics, Management, Accounting and Computer Applications, 2025)
This research explores the influence of green awareness and green attitude on consumers’ intention to purchase green cosmetics in Indonesia. With increasing environmental concerns, understanding the psychological drivers behind eco-friendly product choices is vital, especially in developing markets. The study aims to examine how consumers’ environmental consciousness shapes their attitudes and subsequently affects their intention to buy green cosmetic products. A quantitative method was utilized, involving the distribution of structured questionnaires to individuals familiar with green cosmetics. The data were analyzed using Structural Equation Modeling (SEM). The results confirmed all hypotheses, showing that green awareness significantly influences both green attitude and purchase intention. Additionally, green attitude has a strong positive effect on green purchase intention. These findings underscore the importance of raising consumer awareness and cultivating positive attitudes to promote sustainable purchasing behavior. The study provides practical implications for businesses and policymakers striving to advance environmentally responsible consumption in Indonesia’s cosmetic sector.